Payment System Settlement and Bank Incentives - Kahn, Charles M.; Roberds, William (Review of Financial Studies, 1998)
In this article, we consider the relative merits of net versus gross settlement of interbank payments. Net settlement economizes on the costs of holding non-interest-bearing reserves, but increases moral hazard problems. The "put option" value of default under net settlement can also distort banks' investment incentives. Absent these distortions, net settlement dominates gross, although the optimal net settlement scheme may involve a positive probability of default.